Juridical Implications Of Notaries Who Do Not Maintain Considential Confidentiality Of Consumers In The Conception Of Legal Certainty In The Pekalongan State Court - Rizky, Defiani Amalia (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
.